Water resource selection and optimisation for shale gas developments in Australia: A combinatorial approach. (October 2018) - Gonzalez Cruz, Cesar; Naderpour, Mohsen; Ramezani, Fahimeh
Highlights: MCDM and system dynamics are used to support the sustainable development of shale gas. The methodology aims to achieve a technical, economic, social and environmental balance. AHP is used to determine the optimal water sources. System dynamics is utilized to holistically visualise and understand factor interactions. Abstract: Australia has significant quantities of technically recoverable shale gas and the potential to become a major producer of natural gas from these unconventional resources. However, the hydrocarbon extraction process from shale formations involves heavy drilling and hydraulic fracturing. Both these activities consume a considerable volume of water, which impacts local communities and the environment. This paper proposes a combinatorial methodology that incorporates multi-criteria decision-making and system dynamics to select the best water resources, and then investigate the regional impact of consuming those resources over the long-term. The methodology is described through a case study on the Beetaloo Basin, Northern Territory – a prospective shale gas resources deposit. The results show that the produced water and fresh groundwater are appropriate options for the basin, and appropriate scenarios can prevent the over-extraction of fresh groundwater, maximise the reuse of water, and minimise aquifer disturbance. The proposed methodology is designed to support petroleum companies when making decisions about which water resources to use in shale mining operations to balance various factors affecting the system.